Negative electrode for all-solid-state battery, and all-solid-state battery

By using lithium titanium oxide particles with specific particle size ratio and specific surface area as negative electrode active substances, the problem of insufficient output characteristics of all solid batteries during large current discharge is solved, the resistance value and high energy density of the battery are improved, and the battery is enhanced security.

CN119297201APending Publication Date: 2025-01-10MAXELL LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411393731.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-09-02
Filing Date
2020-08-24
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing all-solid batteries lack the output characteristics during high current discharge, and the lithium titanium oxide secondary particles are prone to disengage during the molding process, resulting in poor electron conductivity and ion conductivity, affecting the performance of the battery.

Method used

Lithium titanium oxide particles with a specific particle size ratio and specific surface area are used as the negative electrode active material, and the particle size distribution is adjusted through the pulverization treatment, so that they are more likely to come into contact with the solid electrolyte and conductive additive during molding, thereby improving the output characteristics of the battery.

Benefits of technology

It achieves excellent output characteristics of all-solid battery, improves the resistance value and high current discharge capacity of the battery, and enhances the high energy density and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297201A_ABST
    Figure CN119297201A_ABST
Patent Text Reader

Abstract

Provided are: an all-solid-state battery having excellent output characteristics; and an all-solid-state battery negative electrode capable of constituting the all-solid-state battery. This negative electrode for an all-solid-state battery is a negative electrode used in an all-solid-state battery, has a molded body of a negative electrode mixture containing a negative electrode active material, a solid electrolyte, and a conductive auxiliary agent, and is characterized in that: the negative electrode active material contains lithium titanium oxide particles having a ratio Dp / D50 of a primary particle diameter Dp to a particle diameter D50 of greater than 0.6 and a specific surface area of 2 m2 / g or more; the measurement of D50 and the specific surface area uses lithium titanium oxide particles obtained in the following order (1) to (4): (1) 0.1 g of a sample is taken from a molded article of the negative electrode mixture; (2) washing with 200 cc of water for two times, placing in 200 cc of water for 12 hours, leaving the part settled in the water, and discarding the supernate; (3) repeating the operation in the step (2) for 10 times; and (4) drying the obtained precipitate at 120 DEG C for 2 hours, and further drying at 60 DEG C for 12 hours.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the original application, with an application date of August 24, 2020, application number 202080060098.3, and invention name “Negative electrode for all-solid-state batteries and all-solid-state batteries”. Technical Field

[0002] The present invention relates to an all-solid-state battery having excellent output characteristics and an all-solid-state battery negative electrode which can constitute the above-mentioned all-solid-state battery. Background Art

[0003] In recent years, with the development of portable electronic devices such as mobile phones and notebook personal computers, and the practical application of electric vehicles, there is an increasing demand for small, lightweight, high-capacity, and high-energy-density secondary batteries.

[0004] At present, in lithium secondary batteries that can meet this requirement, especially lithium ion secondary batteries, the positive electrode active material uses lithium-containing composite oxides such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), and the negative electrode active material uses graphite, etc., and as the non-aqueous electrolyte, an organic electrolyte containing an organic solvent and a lithium salt is used.

[0005] Furthermore, as the application equipment of lithium ion secondary batteries further develops, lithium ion secondary batteries are required to have further improved properties such as longer life, higher capacity, and higher energy density.

[0006] In terms of improving the characteristics of lithium-ion secondary batteries, there are examples of improved positive electrode active materials. For example, Patent Document 1 proposes that the positive electrode active material uses a layered lithium transition metal composite oxide containing nickel, in which the ratio of the average particle size based on electron microscope observation to the average particle size obtained by the cumulative particle size distribution based on a volume basis is set to a specific value or less.

[0007] In addition, lithium-ion secondary batteries are also required to be safe and reliable. However, the organic electrolyte used in lithium-ion secondary batteries contains an organic solvent as a flammable substance, so when an abnormal situation such as a short circuit occurs in the battery, there is a possibility of abnormal heating of the organic electrolyte. In addition, with the trend of high energy density of lithium-ion secondary batteries and increased amount of organic solvent in organic electrolytes in recent years, the safety and reliability of lithium-ion secondary batteries are further required.

[0008] Under the above circumstances, all-solid lithium secondary batteries (all-solid batteries) that do not use organic solvents have attracted much attention. All-solid batteries are batteries that use a molded solid electrolyte that does not use an organic solvent to replace the conventional organic solvent-based electrolyte. There is no concern about abnormal heating of the solid electrolyte, and they are highly safe.

[0009] Improvements in active materials have also been attempted in all-solid batteries. For example, Patent Document 2 proposes a technique for improving the capacity of an all-solid battery during high-current discharge by using materials whose specific surface area and capacitance satisfy a specific relationship for the positive and negative active materials. In addition, Patent Document 3 attempts to improve the battery characteristics of an all-solid battery by using a battery with lithium titanate as an active material so that the active material has good contact with the solid electrolyte particles, wherein the lithium titanate has a specific specific surface area and the average particle size is adjusted so as to have a specific relationship with the average particle size of the solid electrolyte particles.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2017-188445

[0013] Patent Document 2: Japanese Patent Application Publication No. 2003-187876

[0014] Patent Document 3: Japanese Patent Application Publication No. 2012-243644 Summary of the invention

[0015] Problems to be solved by the invention

[0016] Currently, the application fields of all-solid-state batteries are rapidly expanding. For example, from the perspective of application in applications requiring discharge at a large current value, there is a demand for improved output characteristics to cope with such demand.

[0017] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an all-solid-state battery having excellent output characteristics and an all-solid-state battery negative electrode that can constitute the above-mentioned all-solid-state battery.

[0018] Methods for solving problems

[0019] The negative electrode for a solid-state battery of the present invention is characterized in that it has a molded body of a negative electrode mixture containing a negative electrode active material, a solid electrolyte, and a conductive auxiliary agent, wherein the negative electrode active material contains a primary particle size D p With particle size D 50 Ratio D p / D 50 Greater than 0.6 and specific surface area of ​​2m 2 / g or more of lithium titanium oxide particles.

[0020] The all-solid-state battery of the present invention is characterized in that it comprises a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode, and the negative electrode is the negative electrode for the all-solid-state battery of the present invention.

[0021] Effects of the Invention

[0022] According to the present invention, it is possible to provide an all-solid-state battery having excellent output characteristics and an all-solid-state battery negative electrode which can constitute the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cross-sectional view schematically showing an example of the all-solid-state battery of the present invention.

[0024] Figure 2 This is a plan view schematically showing an example of the all-solid-state battery of the present invention.

[0025] Figure 3 for Figure 2 II line cross-sectional view. DETAILED DESCRIPTION

[0026] <Anode for all-solid-state batteries>

[0027] The negative electrode for an all-solid-state battery (hereinafter sometimes simply referred to as “negative electrode”) of the present invention contains lithium titanium oxide as a negative electrode active material.

[0028] Lithium titanium oxide is known as a negative electrode active material for all-solid batteries having a solid electrolyte and lithium ion secondary batteries having an organic electrolyte, and currently used are secondary particles formed by aggregation of fine primary particles.

[0029] The electrodes (positive and negative electrodes) of all-solid-state batteries are sometimes manufactured by the following steps: active materials, solid electrolytes, conductive additives, etc. are mixed without adding solvents to form an electrode mixture (positive electrode mixture or negative electrode mixture), which is then press-formed to form a molded body. When secondary particles of lithium titanium oxide are used as the active material, the secondary particles are often broken into primary particles when the electrode mixture (negative electrode mixture) is formed.

[0030] Inference: If the secondary particles of lithium titanium oxide can be in good contact with the solid electrolyte and the conductive aid when the electrode mixture is modulated, the electronic conductivity and ion conductivity in the negative electrode (in the molded body of the negative electrode mixture) are good by making a molded body while maintaining this state as much as possible, but it is difficult to ensure the contact between the primary particles detached from the secondary particles and the solid electrolyte and the conductive aid during the aforementioned molding. In particular, lithium titanium oxide is a material with low conductivity, so the primary particles detached from the secondary particles are likely not to participate in the charge and discharge reaction of the battery. Moreover, if the proportion of primary particles detached from the secondary particles increases, it is believed that, for example, the output characteristics of the battery are impaired. As shown in the comparative example described later, in the all-solid-state battery with a negative electrode using secondary particles of lithium titanium oxide as the active material, the resistance value (DCR) is large and the output characteristics are poor.

[0031] Therefore, in the negative electrode of the present invention, as the active material, a primary particle size Dp With particle size D 50 Ratio D p / D 50 Greater than 0.6 and specific surface area of ​​2m 2 / g or more of lithium titanium oxide particles, thereby constituting an all-solid-state battery with excellent output characteristics.

[0032] Particle size D of lithium titanium oxide particles 50 It is the particle size at which the cumulative frequency is 50% on a volume basis. When the lithium titanium oxide particles exist as secondary particles, it refers to the secondary particle size. The primary particle size D of the lithium titanium oxide particles p With particle size D 50 Ratio D p / D 50 When the value is greater than 0.6, the aggregation degree of primary particles is small and the ratio of primary particles existing without forming secondary particles is high. p / D 50 Since lithium titanium oxide particles with a gamma-ray diffraction ratio of >0.6 are mostly primary particles, when a negative electrode mixture containing the lithium titanium oxide particles is formed into a molded body by pressure molding or the like, particles that are separated from the secondary particles and do not come into contact with the solid electrolyte or the conductive additive are less likely to be produced.

[0033] In addition, the surface smoothness of the primary particles of ordinary lithium titanium oxide is relatively high, but the specific surface area of ​​the lithium titanium oxide particles according to the present invention is 2 m 2 / g or more, the surface is rough and it is easy to maintain contact with the solid electrolyte and the conductive auxiliary agent.

[0034] The negative electrode of the present invention is believed to be formed by having a specific D p / D 50 The various effects brought about by the lithium titanium oxide particles with a large specific surface area can constitute an all-solid-state battery with excellent output characteristics.

[0035] The negative electrode of the present invention has a molded body of a negative electrode mixture, which contains lithium titanium oxide particles as a negative electrode active material, a solid electrolyte and a conductive additive, etc. Examples thereof include a negative electrode consisting only of the aforementioned molded body, and a negative electrode having a structure in which the aforementioned molded body and a current collector are integrated.

[0036] Examples of the lithium titanium oxide include lithium titanium oxides represented by the following general composition formula (1).

[0037] Li[Li 1 / 3-a M 1 a Ti 5 / 3-b M 2 b ]O4(1)

[0038] In the above general composition formula (1), M 1 is at least one element selected from the group consisting of Na, Mg, K, Ca, Sr and Ba, M 2 It is at least one element selected from the group consisting of Al, V, Cr, Fe, Co, Ni, Zn, Ym, Zr, Nb, Mo, Ta and W, 0≦a<1 / 3, 0≦b≦2 / 3.

[0039] That is, in the lithium titanium oxide represented by the general composition formula (1), a portion of the Li site can be replaced by the element M. 1 Wherein, in the above general composition formula (1), the element M represents 1 The ratio a is preferably less than 1 / 3. In the lithium titanium oxide represented by the above-mentioned general composition formula (1), Li may not be replaced by the element M. 1 Substitution, thus indicating that the element M 1 The ratio of a can be 0.

[0040] In addition, in the lithium titanium oxide represented by the above-mentioned general composition formula (1), the element M 2 It is a component for improving the electronic conductivity of lithium titanium oxide, indicating that the element M 2 When b of the ratio is 0≦b≦2 / 3, a good effect of improving the electron conductivity can be ensured.

[0041] From the viewpoint of increasing the ratio of primary particles and thus being able to construct a battery with excellent output characteristics, the primary particle size D of the lithium titanium oxide particles is p With particle size D 50 Ratio D p / D 50 It should be noted that all lithium titanium oxide particles may be primary particles, so D p / D 50 The preferred upper limit value of is 1.

[0042] It should be noted that since the contact resistance between the lithium titanium oxide particles is large, in order to reduce the number of contact points, the primary particle size (average particle size of the primary particles) of the lithium titanium oxide particles is preferably D p Specifically, D p It is preferably 0.7 μm or more, and more preferably 1.2 μm or more. p The upper limit value is about 10 μm.

[0043] Particle size D of lithium titanium oxide particles 50 As long as D p / D 50 It only needs to be within the range of the aforementioned values.

[0044] The primary particle size D of the lithium titanium oxide particles referred to in this specification is p This value is obtained by selecting 50 particles with recognizable outlines from an image of lithium titanium oxide particles observed at 10,000 times using a scanning electron microscope (SEM), measuring the particle diameters on the major axis of the selected particles, and calculating the average value of all the particles.

[0045] In addition, the particle size D of the lithium titanium oxide particles referred to in this specification is 50 D is the value obtained by using a laser scattering particle size distribution analyzer (e.g., LA-920 manufactured by Horiba, Ltd.) to disperse the particles in a medium that does not dissolve them, and to obtain the particle size at a cumulative frequency of 50% based on volume. 50 The average particle size is also a value obtained by this method.

[0046] From the viewpoint of being able to maintain good contact with the solid electrolyte and the conductive additive and thus forming a battery with excellent output characteristics, the specific surface area of ​​the lithium titanium oxide particles is 2 m 2 In addition, there is no particular upper limit on the specific surface area of ​​lithium titanium oxide, but it is usually 20 m 2 / g or so.

[0047] The specific surface area of ​​lithium titanium oxide particles mentioned in this specification is obtained by measuring and calculating the surface area using the BET formula, which is a theoretical formula for multi-molecular layer adsorption, and is the specific surface area of ​​the active material surface and micropores. Specifically, it is a value obtained as the BET specific surface area using a specific surface area measuring device using a nitrogen adsorption method (e.g., "Macsorb HMmodele-1201" manufactured by Mountech).

[0048] It should be noted that D can also be obtained for lithium titanium oxide extracted from the molded body of the negative electrode mixture. 50 and BET specific surface area.

[0049] As a method for extracting lithium titanium oxide from the molded body of the negative electrode mixture, for example, the following method can be exemplified.

[0050] A 0.1 g sample was collected from the molded body of the negative electrode mixture, washed twice with 200 cc of water, and then placed in 200 cc of water for 12 hours, leaving the part that precipitated in the water and discarding the supernatant. After a series of operations from the above-mentioned washing to discarding the supernatant were repeated 10 times, the obtained precipitate was dried at 120° C. for 2 hours and further dried at 60° C. for 12 hours to obtain lithium titanium oxide in the molded body of the negative electrode mixture.

[0051] D p / D50 The lithium titanium oxide particles having a specific surface area satisfying the above-mentioned value can be obtained by pulverizing secondary particles of lithium titanium oxide to form primary particles. The lithium titanium oxide can be pulverized using, for example, a planetary ball mill.

[0052] For example, by using the above method and conditions to reduce the particle size D 50 The secondary particles of lithium titanium oxide with a size of about 30 to 35 μm are crushed to D p / D 50 The specific surface area of ​​the obtained lithium titanium oxide particles can be adjusted to the above value. Usually, even after the above pulverization treatment, the particle size of the primary particles of lithium titanium oxide constituting the secondary particles will not change significantly. p / D 50 When the above values ​​are adjusted, the D of the lithium titanium oxide particles is mainly adjusted by pulverization. 50 That's it.

[0053] The negative electrode active material may be used together with lithium titanium oxide other than lithium titanium oxide used in lithium ion secondary batteries, etc. The proportion of the negative electrode active material other than lithium titanium oxide in the total amount of the negative electrode active material is preferably 30% by mass or less.

[0054] The solid electrolyte of the negative electrode is not particularly limited as long as it has lithium ion conductivity, and for example, a sulfide-based solid electrolyte, a hydride-based solid electrolyte, an oxide-based solid electrolyte, or the like can be used.

[0055] As sulfide-based solid electrolytes, for example, Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, Li2S-B2S3 glass, etc. can be mentioned. In addition, Li2S-P2S5, which has attracted attention in recent years as a material with high lithium ion conductivity, can also be used. 10 GeP2S 12 (LGPS system), Li6PS5Cl (argyrodite system). Among them, argyrodite system materials having high lithium ion conductivity and high chemical stability are particularly preferably used.

[0056] As hydride-based solid electrolytes, for example, LiBH4, solid solutions of LiBH4 and the following alkali metal compounds (for example, the molar ratio of LiBH4 to the alkali metal compound is 1:1 to 20:1), etc. As the alkali metal compound in the aforementioned solid solution, at least one selected from the group consisting of lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbiF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amides, rubidium amides, and cesium amides can be cited.

[0057] Examples of oxide-based solid electrolytes include Li7La3Zr2O 12 , LiTi(PO4)3, LiGe(PO4)3, LiLaTiO3, etc.

[0058] The solid electrolyte may be one or more of the solid electrolytes exemplified above. Among the solid electrolytes exemplified above, a sulfide-based solid electrolyte is more preferably used because it has high lithium ion conductivity and a function of improving the moldability of the negative electrode mixture.

[0059] It should be noted that even after the negative electrode mixture is press-formed by press-forming or the like, the D p The value of D is almost unchanged compared with that before the pressurization. However, since the sulfide-based solid electrolyte is particularly soft among the solid electrolytes exemplified above, the sulfide-based solid electrolyte is used for the negative electrode, thereby better suppressing the rupture of the primary particles of the lithium titanium oxide when the molded body for forming the negative electrode mixture is pressed, and suppressing the D p , and is therefore preferred.

[0060] As the conductive auxiliary agent of the negative electrode, for example, a carbon material such as graphite or carbon black can be used.

[0061] The negative electrode mixture may or may not contain a binder. When the negative electrode mixture contains a binder, a fluororesin such as polyvinylidene fluoride (PVDF) or the like can be used as the binder.

[0062] When a current collector is used in the negative electrode, the current collector may be made of copper, nickel, stainless steel, or aluminum foil; punched metal, mesh, expanded metal, or foamed metal; or a carbon sheet.

[0063] The negative electrode can be manufactured by the following method: lithium titanium oxide particles, solid electrolytes and conductive aids as active materials are mixed, for example, without using a solvent, and the negative electrode mixture is modulated to form particles, etc. In addition, the molded body of the negative electrode mixture obtained by the above operation can also be laminated to a collector to form a negative electrode.

[0064] Alternatively, the negative electrode mixture may be mixed with a solvent to prepare a negative electrode mixture composition, which may be applied to a substrate such as a current collector or a solid electrolyte layer facing the negative electrode, dried, and then pressurized to form a negative electrode mixture molded body.

[0065] The solvent used in the negative electrode mixture composition is preferably selected to be difficult to degrade the solid electrolyte. In particular, sulfide-based solid electrolytes and hydride-based solid electrolytes will react chemically due to trace amounts of water, so it is preferred to use non-polar aprotic solvents represented by hydrocarbon solvents such as hexane, heptane, octane, nonane, decane, decalin, toluene, and xylene. It is especially preferred to use a super dehydrated solvent with a water content of less than 0.001 mass% (10ppm). In addition, fluorine-based solvents such as "Vertrel (registered trademark)" made by Mitsui-DuPont Fluorine Chemicals, "ZEORORA (registered trademark)" made by Japan Zeon Co., Ltd., and "Novec (registered trademark)" made by Sumitomo 3M Co., Ltd., as well as non-aqueous organic solvents such as dichloromethane and ether can also be used.

[0066] As the composition of the negative electrode mixture, for example, the content of the negative electrode active material is preferably 50 to 80% by mass, the content of the solid electrolyte is preferably 20 to 50% by mass, and the content of the conductive aid is preferably 0.1 to 10% by mass. In addition, when the negative electrode mixture contains a binder, its content is preferably 0.1 to 10% by mass. Furthermore, the thickness of the molded body of the negative electrode mixture (including both the case where the negative electrode does not have a collector and the case where it has a collector) is preferably 50 to 1000 μm.

[0067] The negative electrode mixture is molded by using D p / D 50 The lithium titanium oxide particles having a specific surface area satisfying the above value can increase the density (calculated from the mass per unit area and thickness of the negative electrode mixture molded body) to 2.0 g / cm 3 The above can realize the high capacity and high energy density of all-solid batteries. It should be noted that the molded body of the negative electrode mixture does not need to be a porous body like the negative electrode of a battery with an organic electrolyte, so the upper limit of its density is the value calculated by the density of each material constituting the negative electrode mixture (theoretical density).

[0068] <All-solid-state battery>

[0069] The all-solid-state battery of the present invention comprises a positive electrode, a negative electrode, and a solid electrolyte layer present between the positive electrode and the negative electrode, wherein the negative electrode is a negative electrode for the all-solid-state battery of the present invention.

[0070] A cross-sectional view schematically showing an example of the all-solid-state battery of the present invention is shown in Figure 1 . Figure 1 The all-solid-state battery 1 shown has a positive electrode 10 , a negative electrode 20 , and a solid electrolyte layer 30 between the positive electrode 10 and the negative electrode 20 enclosed in an outer casing formed of an outer casing 40 , a sealing can 50 , and a resin gasket 60 interposed therebetween.

[0071] The sealing can 50 is fitted with the opening of the outer can 40 via the gasket 60 , and the opening end of the outer can 40 is tightened inward, whereby the gasket 60 abuts against the sealing can 50 , thereby sealing the opening of the outer can 40 and forming a sealed structure inside the element.

[0072] The outer can and the sealing can can use stainless steel components. In addition, the raw materials of the gasket can use polypropylene, nylon, etc. In addition, when heat resistance is required for the battery use, fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), polyetheretherketone (PEEK) and other heat-resistant resins with a melting point exceeding 240°C can also be used. In addition, when the battery is used for applications requiring heat resistance, its seal can also be sealed with glass airtightness.

[0073] also, Figure 2 and Figure 3 A drawing schematically showing another example of the all-solid-state battery of the present invention is shown. Figure 2 is the plan view of the all-solid-state battery. Figure 3 for Figure 2 II line cross-sectional view.

[0074] Figure 2 and Figure 3 The all-solid-state battery 100 shown contains an electrode body 200 composed of a positive electrode, a solid electrolyte layer, and a negative electrode of the present invention in a laminated film outer body 500 composed of two metal laminated films, and the laminated film outer body 500 is sealed by thermally fusing the upper and lower metal laminated films at its periphery. It should be noted that Figure 3 In order to avoid complicating the drawing, the layers constituting the laminated film outer package 500 and the positive electrode, negative electrode, and separator constituting the electrode body are not shown separately.

[0075] The positive electrode of the electrode body 200 is connected to the positive electrode external terminal 300 in the battery 100. Although not shown in the figure, the negative electrode of the electrode body 200 is also connected to the negative electrode external terminal 400 in the battery 100. In addition, one end side of the positive electrode external terminal 300 and the negative electrode external terminal 400 is led out to the outside of the laminate film outer body 500 in a manner that can be connected to an external device or the like.

[0076] (positive electrode)

[0077] The positive electrode of an all-solid-state battery contains a positive electrode active material and, in addition, usually also contains a solid electrolyte.

[0078] The positive electrode active material is not particularly limited as long as it is a positive electrode active material used in conventional lithium ion secondary batteries, that is, an active material that can absorb and release Li ions. Specific examples of positive electrode active materials include LiM x Mn 2-x O4 (wherein M is at least one element selected from the group consisting of Li, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Fe, Co, Ni, Cu, Al, Sn, Sb, In, Nb, Mo, W, Y, Ru and Rh, 0.01 ≤ x ≤ 0.5) represented by a spinel lithium manganese composite oxide, Li x Mn (1-y-x) Ni y M z O (2-k) F l (wherein M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr and W, 0.8≦x≦1.2, 0<y<0.5, 0≦z≦0.5, k+l<1, -0.1≦k≦0.2, 0≦l≦0.1) a layered compound represented by 1-x M x Lithium cobalt composite oxide represented by LiNi O2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0 ≤ x ≤ 0.5) 1-x M x Lithium nickel composite oxide represented by LiM O2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0 ≤ x ≤ 0.5) 1-x N x Olivine-type composite oxide represented by PO4 (wherein M is at least one element selected from the group consisting of Fe, Mn and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≦x≦0.5), Li4Ti5O 12 The lithium-titanium composite oxides and the like shown above may be used alone or in combination of two or more.

[0079] The solid electrolyte of the positive electrode may be one or more of the same substances as those exemplified above as the solid electrolyte usable in the negative electrode. In order to achieve better battery characteristics, it is preferred to contain a sulfide-based solid electrolyte.

[0080] The positive electrode can, for example, be a structure in which a layer (positive electrode mixture layer) consisting of a positive electrode mixture containing a positive electrode active material and a solid electrolyte, and further a conductive aid and a binder added as needed is formed on one or both sides of a collector, or a molded body (positive electrode mixture molded body) in which the positive electrode mixture is pressure-molded into particles.

[0081] As the binder of the positive electrode, for example, a fluororesin such as polyvinylidene fluoride (PVDF) can be used. In addition, as the conductive auxiliary agent of the positive electrode, for example, a carbon material such as carbon black can be used.

[0082] When a current collector is used in the positive electrode, the current collector may be made of a foil of a metal such as aluminum or stainless steel; a punched metal, a mesh, an expanded metal, a foamed metal; a carbon sheet, or the like.

[0083] When manufacturing a positive electrode, for example, in the case of a positive electrode with a current collector, the following method can be used: the positive electrode active material and the solid electrolyte, and further conductive aids, binders, etc. added as needed are dispersed in a solvent such as xylene to obtain a positive electrode mixture composition (paste, slurry, etc.), the positive electrode mixture composition is applied to the collector, and after drying, it is pressed and formed by calendering or the like as needed to form a layer of the positive electrode mixture (positive electrode mixture layer) on the surface of the collector.

[0084] The solvent used in the positive electrode mixture composition is also the same as the solvent used in the negative electrode mixture composition. It is preferred to select a solvent that is unlikely to degrade the solid electrolyte. It is preferred to use the various solvents previously exemplified as solvents for the negative electrode mixture composition. It is particularly preferred to use a super dehydrated solvent with a water content of less than 0.001 mass % (10 ppm).

[0085] In the case of a positive electrode formed of a molded body of a positive electrode mixture, the positive electrode active material and a solid electrolyte, and a conductive aid, a binder, etc. added as needed, can be mixed to form a positive electrode mixture, which can be compressed by press molding or the like.

[0086] As the composition of the positive electrode mixture in the positive electrode, for example, the content of the positive electrode active material is preferably 50 to 90% by mass, the content of the solid electrolyte is preferably 10 to 50% by mass, and the content of the binder is preferably 0.1 to 10% by mass. In addition, when the positive electrode mixture contains a conductive auxiliary agent, its content is preferably 0.1 to 10% by mass. Furthermore, the thickness of the positive electrode mixture layer in the positive electrode having a collector and the thickness of the positive electrode mixture molded body are preferably 50 to 1000 μm.

[0087] (Solid electrolyte layer)

[0088] The solid electrolyte in the solid electrolyte layer of the all-solid-state battery can use one or more of the same substances as those exemplified above as the solid electrolyte of the negative electrode. Among them, in order to make the battery characteristics more excellent, it is preferred to contain a sulfide-based solid electrolyte, and it is more preferred that the positive electrode, the negative electrode and the solid electrolyte layer all contain a sulfide-based solid electrolyte.

[0089] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.

[0090] The solid electrolyte layer can be formed by the following methods, etc.: a method of compressing the solid electrolyte by pressure molding, etc.; a method of applying a solid electrolyte layer-forming composition prepared by dispersing the solid electrolyte in a solvent on a substrate, a positive electrode, and a negative electrode and drying it, and performing pressure molding such as pressurization as needed, etc.

[0091] The solvent used in the composition for forming a solid electrolyte layer is also the same as the solvent used in the negative electrode mixture containing composition. It is preferred to select a solvent that is unlikely to deteriorate the solid electrolyte. It is preferred to use the various solvents previously exemplified as solvents for the negative electrode mixture containing composition, and it is particularly preferred to use a super dehydrated solvent with a water content of less than 0.001 mass % (10 ppm).

[0092] The thickness of the solid electrolyte layer is preferably 100 to 200 μm.

[0093] (Electrode body)

[0094] The positive electrode and the negative electrode can be used in a battery in the form of a stacked electrode body in which the positive electrode and the negative electrode are stacked with a solid electrolyte layer interposed therebetween, or in the form of a wound electrode body in which the stacked electrode body is wound.

[0095] In addition, from the viewpoint of improving the mechanical strength of the electrode body, when forming the electrode body, it is preferable to perform pressure molding in a state where the positive electrode, the negative electrode, and the solid electrolyte layer are stacked.

[0096] (Battery form)

[0097] All-solid-state batteries can be in the form of: Figure 1 The battery has an outer casing composed of an outer can, a sealing can and a sealing gasket, which is generally called a coin-shaped battery or a button-shaped battery; Figure 2 and Figure 3 The form of the outer casing as shown has a resin film or a metal-resin laminated film; in addition, it can also be a form of the outer casing having a metal bottomed cylindrical (cylindrical, prismatic) outer can and a sealing structure for sealing its opening.

[0098] Example

[0099] Hereinafter, the present invention will be described in detail based on examples, but the following examples are not intended to limit the present invention.

[0100] Example 1

[0101] (Formation of Solid Electrolyte Layer)

[0102] 80 g of sulfide-based solid electrolyte (Li6PS5Cl) was placed in a powder molding mold with a diameter of 10 mm and pressure-molded using a press to form a solid electrolyte layer.

[0103] (Production of negative electrode)

[0104] Planetary ball mill 50 The lithium titanate (Li4Ti5O 12 ) are pulverized to obtain lithium titanate particles used as negative electrode active materials. The obtained lithium titanate particles are D p :1.3μm、D 50 :2.14μm、D p / D 50 : 0.61, specific surface area: 2.70m 2 / g.

[0105] The lithium titanate particles, the sulfide-based solid electrolyte, and the graphite powder as a conductive aid are mixed in a mass ratio of 60:8.5:31.5, and kneaded thoroughly to prepare a negative electrode mixture. Next, 15 mg of the negative electrode mixture is added to the solid electrolyte layer in the powder molding mold, and a press is used to perform pressure molding to form a negative electrode composed of a negative electrode mixture molded body on the solid electrolyte layer. It should be noted that the D of the lithium titanate in the negative electrode mixture molded body after pressure molding is p There was no change compared to before press molding, which was 1.3 μm.

[0106] (Formation of Laminated Electrode Body)

[0107] As the counter electrode, an electrode formed by molding Li metal and In metal into cylindrical shapes and bonding them together was used. The counter electrode was placed on the surface of the solid electrolyte layer opposite to the negative electrode in the aforementioned powder molding mold, and pressure-molded using a press to produce a stacked electrode body.

[0108] (Assembly of model battery)

[0109] Using the aforementioned stacked electrode body, a planar structure and Figure 2A solid-state battery (model battery) having the same structure as shown. On the surface of the aluminum laminate film constituting the laminate film outer body that becomes the inner side of the outer body, the negative electrode collector foil (SUS foil) and the counter electrode collector foil (SUS foil) are pasted side by side laterally with a certain degree of spacing between them. Each of the collector foils is a member cut into the following shape: a main body portion opposite to the negative electrode side surface or the counter electrode side surface of the aforementioned stacked electrode body, and a portion protruding from the aforementioned main body portion to the outside of the battery that becomes the negative electrode external terminal 400 and the counter electrode external terminal 300.

[0110] The aforementioned stacked electrode body is placed on the negative electrode collector foil of the aforementioned laminated film outer package, and the aforementioned stacked electrode body is wrapped with the aforementioned laminated film outer package in a manner that the counter electrode collector foil is arranged on the counter electrode of the aforementioned stacked electrode body. The remaining three sides of the aforementioned laminated film outer package are sealed by thermal fusion under vacuum to obtain a model battery.

[0111] Example 2

[0112] The operation was carried out in the same manner as in Example 1 except that the rotation speed of the planetary ball mill was changed to grind the lithium titanate secondary particles to obtain D p :1.3μm、D 50 :1.86μm、D p / D 50 : 0.70, specific surface area: 4.19m 2 / g of lithium titanate as the negative electrode active material. Then, a model battery was prepared in the same manner as in Example 1 except that the lithium titanate particles were used. It should be noted that the D p There was no change compared to before press molding, which was 1.3 μm.

[0113] Example 3

[0114] The operation was carried out in the same manner as in Example 1 except that the rotation speed of the planetary ball mill was changed to grind the lithium titanate secondary particles to obtain D p :1.3μm、D 50 :2.02μm、D p / D 50 : 0.64, specific surface area: 4.00m 2 / g of lithium titanate as the negative electrode active material. Then, a model battery was prepared in the same manner as in Example 1 except that the lithium titanate particles were used. It should be noted that the D p There was no change compared to before press molding, which was 1.3 μm.

[0115] Comparative Example 1

[0116] D50 A model battery was prepared in the same manner as in Example 1 except that the lithium titanate secondary particles with a size of 7.3 μm were used as the negative electrode active material without being crushed. p :0.5μm、D p / D 50 : 0.07, specific surface area: 10.90m 2 / g. In addition, the D of lithium titanate in the negative electrode mixture molded body after pressure molding is p There was no change compared to before press molding, which was 0.5 μm.

[0117] Comparative Example 2

[0118] D 50 A model battery was prepared in the same manner as in Example 1 except that the lithium titanate secondary particles with a size of 4.53 μm were used as the negative electrode active material without being crushed. p :0.8μm、D p / D 50 : 0.18, specific surface area: 2.50m 2 / g. In addition, the D of lithium titanate in the negative electrode mixture molded body after pressure molding is p There was no change compared to before press molding, which was 0.8 μm.

[0119] Comparative Example 3

[0120] D 50 A model battery was prepared in the same manner as in Example 1 except that the lithium titanate secondary particles with a size of 5.53 μm were used as the negative electrode active material without being crushed. p :2.5μm、D p / D 50 : 0.45, specific surface area: 2.20m 2 / g. In addition, the D of lithium titanate in the negative electrode mixture molded body after pressure molding is p There was no change compared to before press molding, which was 2.5 μm.

[0121] The output characteristics of the model batteries having the negative electrodes of the examples and comparative examples were evaluated under the following conditions. First, each model battery was subjected to a pressure of (1 t / cm 2) state, constant current charging was performed at a current value of 0.05C until the voltage reached 0.38V, then constant voltage charging was performed at a voltage of 0.38V until the current value reached 0.01C, and then discharged at 0.05C to 1.88V. Next, for each model battery, constant current charging was performed at a current value of 0.05C until the voltage reached 0.38V, then constant voltage charging was performed at a voltage of 0.38V until the current value reached 0.01C, and then discharged at a current value of 0.05C until the depth of charge (SOC) was 50%, and then stopped for 1 hour. For each subsequent model battery, the voltage was obtained after a 10-second pulse discharge at a current value of 0.05C, and the DCR was calculated from the value. The smaller the DCR obtained by this method, the better the output characteristics of the model battery (the larger the capacity during large current discharge), and it can be said that the negative electrode of the model battery can constitute an all-solid-state battery with excellent output characteristics.

[0122] The D of the lithium titanate particles used in the negative electrodes of the examples and comparative examples was p / D 50 The values ​​of the specific surface area and the above-mentioned evaluation results are shown in Table 1. In addition, the "DCR" of the model battery in Table 1 is expressed as a relative value when the value of Example 2 is set to 100.

[0123] [Table 1]

[0124]

[0125] As shown in Table 1, the p / D 50 The model batteries of the negative electrodes of Examples 1 to 3 using lithium titanium oxide (lithium titanate) particles having an appropriate specific surface area as the negative electrode active material had small DCR values ​​and excellent output characteristics.

[0126] In contrast, the use of D p / D 50 The DCR values ​​of the negative electrode model batteries of Comparative Examples 1 to 3 in which inappropriate lithium titanium oxide particles (secondary particles) are used as negative electrode active materials are large and the output characteristics are poor. It should be noted that although the lithium titanium oxide particles used in Comparative Examples 1 to 3 have a relatively large specific surface area, this is not caused by the rough surface state of the primary particles, but because they are secondary particles formed by the aggregation of primary particles, and their large specific surface area itself is considered to be unhelpful in improving the contact between the lithium titanium oxide particles (primary particles contained in the secondary particles, primary particles separated from the secondary particles) and the solid electrolyte and the conductive additive.

[0127] Without departing from the scope of the present invention, the present invention may also be implemented in a manner other than the above. The embodiments disclosed in this application are examples, and the present invention is not limited by these embodiments. Compared with the description of the above specification, the scope of the present invention is interpreted with priority by the description of the attached claims, and all changes within the scope equivalent to the claims are included in the claims.

[0128] Industrial Availability

[0129] The all-solid-state battery of the present invention can be used in the same applications as conventionally known secondary batteries, and because it has a solid electrolyte instead of an organic electrolyte solution, it has excellent heat resistance and can be preferably used in applications exposed to high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0131] 1. 100 all-solid-state battery

[0132] 10 Positive electrode

[0133] 20 negative electrode

[0134] 30Solid electrolyte layer

[0135] 40 external cans

[0136] 50 Sealing Cans

[0137] 60 Sealing pad

[0138] 200 electrode body

[0139] 300 positive external terminal

[0140] 400 negative external terminal

[0141] 500 laminated film outer body.

Claims

1. A negative electrode for an all-solid-state battery, characterized in that: It is the negative electrode used in all-solid-state batteries. A molded body having a negative electrode mixture containing a negative electrode active material, a solid electrolyte and a conductive aid, As the negative electrode active material, the primary particle size D p With particle size D 50 Ratio D p / D 50 Greater than 0.6 and specific surface area of ​​2m 2 / g or more lithium titanium oxide particles, Here, D 50 The specific surface area was measured using lithium titanium oxide particles obtained by the following steps (1) to (4): (1) taking a 0.1 g sample from the molded body of the negative electrode mixture; (2) After washing twice with 200 cc of water, place in 200 cc of water for 12 hours, keep the part that settles in the water, and discard the supernatant; (3) Repeat the step (2) 10 times; (4) The obtained precipitate was dried at 120°C for 2 hours and further dried at 60°C for 12 hours.

2. The all-solid-state battery negative electrode according to claim 1, wherein the lithium titanium oxide particles have a D p It is not less than 0.7 μm and not more than 10 μm. 3 . The all-solid-state battery negative electrode according to claim 1 , wherein the solid electrolyte is a sulfide-based solid electrolyte. 4 . The negative electrode for an all-solid-state battery according to claim 3 , wherein the solid electrolyte is an argyrodite-based sulfide-based solid electrolyte.

5. The all-solid-state battery negative electrode according to any one of claims 1 to 4, The lithium titanium oxide includes a lithium titanium oxide represented by the following general composition formula (1): It[It 1 / 3-a M 1 a Small 5 / 3-b M 2 b ]O4(1) In the general composition formula (1), M 1 is at least one element selected from the group consisting of Na, Mg, K, Ca, Sr and Ba, M 2 It is at least one element selected from the group consisting of Al, V, Cr, Fe, Co, Ni, Zn, Ym, Zr, Nb, Mo, Ta and W, 0≦a<1 / 3, 0≦b≦2 / 3.

6. An all-solid-state battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a solid electrolyte layer between the positive electrode and the negative electrode, wherein the negative electrode is the negative electrode for an all-solid-state battery according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2003187876A

  • Electrode and all-solid state nonaqueous electrolyte battery

    JP2012243644A

  • Positive electrode active material for nonaqueous electrolyte secondary battery

    JP2017188445A